A systematic review of the public–private partnership literature published between 2012 and 2021 - Fu, Liping; Sun, Huajun; Fang, Ya’nan; Xu, Kaibo (Journal of Civil Engineering and Management, 2023)
After approximately 30 years of development, public-private partnership (PPP) has attracted increased attention as an alternative procurement paradigm. However, fresh research on PPP has emerged in the last decade that needs to be summarized. This study selects publications on PPP that were published in recognized journals between 2012 and 2021 from the Scopus database. In target publications, methodologies employed, contributions made, and fields applied are summarized. Social network analysis is used to summarize five core topics in PPP from a multidisciplinary perspective; they are risk management, contract management, CFFs and CSFs, economic and financial issues, and performance management. Additionally, the research limitations and future development direction of PPP are also examined. This study can shed some light on future research on PPP and can contribute to the practice of PPP.